The effects of climate risk on hydropower P3 contract value: Preliminary study of the Inga 3 Dam - A. Richard Swanson; Vivek Sakhrani (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2016)
Large hydropower dams are at the centre of a debate weighing the value and costs of renewable energy against the risks of climate change. The debate is especially relevant on the African continent, which offers vast hydropower potential, but which is exposed to possible climatic changes. This paper presents one possible framework for analysing, valuing, and mitigating the possible impacts of climate change on investment returns. It applies the framework to the proposed series of Inga projects. We find that project concessions can recapture value by phasing dam build-out. Our optionality framework can help structure P3 contracts to improve hydropower project value as well as insure sponsors against climate risk.
Keywords: O20; 330; hydropower; energy; electricity; environment; Africa